Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Kemampuan Literasi Sains Peserta Didik Kelas V SDN Karangtanjung Pada Materi Cahaya dan Sifatnya - Ningrum, Lintang Ayu; Lestari, Wahyu Maulida (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to determine the effect of the guided inquiry learning model on the science literacy skills of fifth-grade students at SDN Karangtanjung in the topic of light and its properties. The research employed a quantitative approach using a one-group pretest-posttest design. The instrument consisted of 20 multiple-choice items, of which 18 were declared valid after validation. A reliability test showed a Cronbach’s Alpha value of 0.794. The Shapiro-Wilk test confirmed that the data were normally distributed, and a paired sample t-test yielded a significance value of 0.000 (< 0.05), indicating a significant difference between the pretest and posttest. The average score increased from 53.73 to 85.27. The highest improvement occurred in the indicator of interpreting data and scientific evidence (84.69%), followed by designing and evaluating scientific inquiry (68.42%), and explaining scientific phenomena (28.12%). These findings suggest that the guided inquiry model is effective in enhancing science literacy through active, exploratory, and experience-based learning.